ХАЛҚ ЎЙИНЛАРИ- БАРКАМОЛ ШАХС ТАРБИЯСИДА МУҲИМ ПЕДАГОГИК ОМИЛ - Абдуллаев, А.А. (SCIENCE and SOCIETY, 2016)
The article deals with the meaning of national games as an important pedagogical factor in the upbringing of harmonious personality. The author gives recommendations how to use them at the lessons with the purpose of increasing students‘ activeness .
Keywords: healthy generation; personality; folk games; pedagogical factor; activeness; lesson; students; ways and means